New Mediterranean Biodiversity Records (April 2015) - Α. ΖΕΝΕΤΟΣ; E.H.KH. AKEL; C. APOSTOLIDIS; M. BILECENOGLU; G. BITAR; V. BUCHET; N. CHALARI; M. CORSINI-FOKA; F. CROCETTA; A. DOGRAMMATZI; M. DRAKULIĆ; G. FANELLI; et al. (Mediterranean Marine Science, 2015)
The Collective Article ‘New Mediterranean Biodiversity Records’ of the Mediterranean Marine Science journal offers the means to publish biodiversity records in the Mediterranean Sea. The current article is divided in two parts, for records of native and alien species respectively. The new records of native fish species include: the slender sunfish Ranzania laevis and the scalloped ribbonfish Zu cristatus in Calabria; the Azores rockling Gaidropsarus granti in Calabria and Sicily; the agujon needlefish Tylosurus acus imperialis in the Northern Aegean; and the amphibious behaviour of Gouania willdenowi in Southern Turkey. As regards molluscs, the interesting findings include Ischnochiton usticensis in Calabria and Thordisa filix in the bay of Piran (Slovenia). The stomatopod Parasquilla ferussaci was collected from Lesvos island (Greece); the isopod Anilocra frontalis was observed parasitizing the alien Pteragogus trispilus in the Rhodes area. The asteroid Tethyaster subinermis and the butterfly ray Gymnura altavela were reported from several localities in the Greek Ionian and Aegean Seas. The new records of alien species include: the antenna codlet Bregmaceros atlanticus in Saronikos Gulf; three new fish records and two decapods from Egypt; the establishment of the two spot cardinal fish Cheilodipterus novemstriatus and the first record of the Indo-Pacific marble shrimp Saron marmoratus in semi-dark caves along the Lebanese coastline; the finding of Lagocephalus sceleratus, Sargocentron rubrum, Fistularia commersonii and Stephanolepis diaspros around Lipsi island (Aegean Sea, Greece); the decapod Penaeus hathor in Aegean waters; the decapod Penaeus aztecus and the nudibranch Melibe viridis in the Dodecanese islands; the finding of Pinctada imbricata radiata in the Mar Grande of Taranto (Ionian Sea, Italy) and the Maliakos Gulf (Greece).